IEEE InternationalElectron Devices Meeting, 2005. IEDM Technical Digest.
DOI: 10.1109/iedm.2005.1609364
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and breakdown of 0.9 nm EOT SiO/sub 2/ ALD HfO/sub 2/metal gate stacks under positive constant voltage stress

Abstract: By means of leakage current measurements, charge pumping and TDDB analysis, we construct a consistent model for the degradation and breakdown of 0.9 nm EOT Atomic Layer Deposited (ALD) HfO 2 . During degradation, traps and two-trap clusters are formed in the HfO 2 giving rise to considerable SILC. The two-trap clusters subsequently wear out, finally leading to an abrupt hard breakdown. We demonstrate that 0.9 nm EOT ALD HfO 2 is intrinsically reliable under Constant Voltage Stress if hard breakdown is used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…Up to now, the sequence of breakdown has remained a mystery with contradicting results and no unified understanding to leverage on. While some groups suggest HK to be the first to breakdown [21] - [23], others indicate IL to be the weakest link [24] - [30]. Without having a universal understanding on the breakdown sequence, it is difficult to proceed further in analyzing the post-BD phase of degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the sequence of breakdown has remained a mystery with contradicting results and no unified understanding to leverage on. While some groups suggest HK to be the first to breakdown [21] - [23], others indicate IL to be the weakest link [24] - [30]. Without having a universal understanding on the breakdown sequence, it is difficult to proceed further in analyzing the post-BD phase of degradation.…”
Section: Introductionmentioning
confidence: 99%
“…It can be clearly observed that the Weibull-slope (β) increases with elevated stress voltages. We attribute the variations on slopes to the competition of breakdown in a bilayer dielectric stack, consisting of SiO 2 and high-k [20]- [21]. Note that the traditional Weibull fitting is not applicable with this varying slopes, and the limited number of samples is not sufficient to characterize the bimodal distribution.…”
Section: B Forming Analysismentioning
confidence: 99%
“…Note however that the current in the region of the fit is in the micro-amp range, suggesting that 2-trap conduction is already dominant. If this is the case then, as shown by Degraeve et al [10], the SILC generation rate would be twice the TDDB trap generation rate.…”
Section: Stress Induced Leakage Current Analysismentioning
confidence: 95%
“…To further investigate the possibility of a high defect generation rate in these devices we examined the I-t traces during stress. It has been shown that subtracting the initial charging component from the I-t trace, the pure leakage during the stress can be extracted [10]. This is shown in figure 4a for the SiGe devices.…”
Section: Stress Induced Leakage Current Analysismentioning
confidence: 96%